Ceramic tile with color enamel decoration effect on surface and preparation method of ceramic tile
By applying base glaze on the surface of the ceramic tile, printing color patterns, positioning metal dry particles, applying glass dry particles and spraying suspended glaze slurry, the problem of poor enameled decoration effect on the surface of the ceramic tile in the prior art is solved, efficient and stable enamel decorative effect is achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411666034.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
When used on the surface of ceramic tile, existing enamel decorative technology has problems such as mismatch in material characteristics, complexity of process and high cost, unstable decorative effect and limited scope of application.
The method of applying base glaze on the surface of the ceramic tile blank, printing color patterns, positioning metal dry particles, printing glue, applying glass dry particles, spraying suspended glaze slurry and firing them is used to prepare ceramic tiles with enamel decorative effects on the surface.
It realizes the clear image line contour on the surface of the tile, enhances the three-dimensional and artistic sense of the pattern, reduces production costs, improves production efficiency, and ensures the durability and stability of the decorative effect.
Smart Images

Figure CN119841669A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of architectural decoration building materials, and in particular to a ceramic tile with enamel decorative effect on the surface and a preparation method thereof. Background Art
[0002] The existing enamel decoration technology is mainly used in the fields of aluminum alloy curtain wall panels, steel plates, titanium alloy cloisonné enamel crafts, enamel building components and precious metal local decoration. However, the existing enamel decoration technology has many shortcomings when applied to the surface of ceramic tiles, including:
[0003] 1. Mismatch in material properties: Due to the significant differences in the material properties of ceramic tiles and commonly used materials for existing enamel decoration technologies such as aluminum alloy, steel, and titanium alloy, the direct application of these technologies will lead to poor decorative effects and even damage the surface of the ceramic tiles.
[0004] 2. Process complexity and high cost: When the existing cloisonné enamel, cloisonné glue enamel and other processes are implemented on tiles, not only the process flow is complicated, but also the cost is high, which is not suitable for large-scale production of tiles.
[0005] 3. Unstable decorative effect: The application effect of some enamel decoration technologies on tiles is unstable, and problems such as color fading and dry particle falling off are prone to occur, affecting the durability and aesthetics of the decorative effect.
[0006] 4. Limited scope of application: Existing enamel decoration technologies are mostly designed for specific materials or specific decoration needs, and lack universal technology suitable for large-area decoration of tile surfaces.
[0007] Therefore, it is necessary to develop a method suitable for the enamel decorative effect on the surface of ceramic tiles. Summary of the invention
[0008] The purpose of the present application is to provide a ceramic tile with an enamel decorative effect on the surface and a preparation method thereof, aiming to solve the problem that the existing cloisonné enamel, cloisonné glue enamel and other processes are applied to ceramic tiles with high cost, complex process and are not suitable for large-scale production of ceramic tiles.
[0009] To achieve the above objectives, the present application provides a method for preparing a ceramic tile having an enamel decorative effect on the surface, comprising:
[0010] Apply base glaze and print color patterns on the surface of the tile blank in sequence;
[0011] Positioning metal dry particles on the tile blank formed with a color pattern to obtain the outline of the image lines outlined by the metal dry particles;
[0012] Print glue patterns, apply glassy dry particles, and spray suspended glaze slurry on the surface of the tile blank with image line contours;
[0013] The ceramic tile blanks sprayed with the suspended glaze slurry are fired to obtain ceramic tiles with enamel color decorative effects on the surface.
[0014] In some embodiments, the metal dry particles include one or more of aluminum powder, copper powder, and iron powder;
[0015] And / or, the particle size of the metal dry particles is 0.1-0.5 mm.
[0016] In some embodiments, the metal dry particles are positioned by dispensing with a dispensing machine;
[0017] Alternatively, the metal dry particles are positioned by electrostatic adsorption by applying an electrostatic field on the surface of the tile blank.
[0018] In some embodiments, the positioning of the metal dry particles satisfies at least one of the following features AC:
[0019] A. The dispensing speed of the dispensing machine is 10-20 times / second, the dispensing pressure is 0.2-0.5 MPa, the needle diameter of the dispensing machine is 0.2-0.5 mm, and the distance between the needle of the dispensing machine and the surface of the tile blank is maintained at 2-5 mm;
[0020] B. The glue used in the dispensing machine is selected from bisphenol A epoxy resin;
[0021] C. The dispensing machine is a double-liquid dispensing machine, and the glue used by the double-liquid dispensing machine includes glue A and glue B, and the glue A and the glue B are mixed in a mass ratio of 1:1 to 2:1;
[0022] D. The voltage of the electrostatic field is 10-30 kilovolts, the action time of the electrostatic field is 5-10 seconds, and the distance between the electrode applying the electrostatic field and the surface of the tile blank is 5-10 centimeters.
[0023] In some embodiments, the viscosity of the glue used to print the glue pattern is 500-1000 centipoise;
[0024] And / or, the printing speed of the printed glue pattern is 10-20 m / min;
[0025] And / or, the glue used for printing the glue pattern is acrylate glue; preferably, the acrylate glue is one or both of epoxy-modified acrylate glue and polyurethane-modified acrylate glue.
[0026] In some embodiments, the step of donating vitreous dry particles satisfies at least one of the following conditions:
[0027] a. The vitreous dry particles are barium-containing vitreous dry particles;
[0028] b. The glassy dry particles are barium-containing glassy dry particles, and the barium-containing glassy dry particles include, by mass percentage: SiO2 55%-65%, BaO 15%-20%, Al2O3 10%-15% and Na2O 5%-10%;
[0029] c. more than 80 wt % of the glassy dry particles have a particle size between 0.1 and 0.5 mm;
[0030] d. The Mohs hardness of the glassy dry particles is between 5 and 7;
[0031] e. The thermal expansion coefficient of the glassy dry particles is 50×10 -7 / ℃-80×10 -7 / ℃;
[0032] f. The application rate of the glassy dry particles is 5-10 g / sec;
[0033] The dispensing accuracy of the glassy dry particles is ±0.1 mm.
[0034] h. After applying the vitreous dry particles, a suction device is used to suck away the unbound vitreous dry particles; the suction force of the suction device is 10-20 Newtons, the diameter of the suction nozzle is 10-30 mm, and the action time is 5-10 seconds.
[0035] In some embodiments, the thickness of the bottom glaze is 0.1-0.3 mm;
[0036] And / or, the viscosity of the base glaze tested by applying a No. 4 cup is 30-50 seconds and the specific gravity is 1.5-1.8 g / cm3;
[0037] And / or, the color pattern is printed by a digital inkjet printer, the resolution of the digital inkjet printer is 300-600 dpi, and the viscosity of the ink is 10-20 centipoise.
[0038] In some embodiments, the mass concentration of the suspending agent in the suspended glaze slurry is 40-60%;
[0039] And / or, the spraying pressure is 0.3-0.5 MPa;
[0040] And / or, the thickness of the suspended glaze slurry is 0.2-0.4 mm.
[0041] In some embodiments, the firing temperature is 1100-1300° C., and the firing time is 30-60 minutes.
[0042] The present application also provides a ceramic tile with an enamel decorative effect on the surface, which is prepared by the above-mentioned method for preparing a ceramic tile with an enamel decorative effect on the surface.
[0043] Compared with the prior art, the beneficial effects of this application include:
[0044] In the present application, metal dry particles are positioned on the ceramic tile blank with a color pattern, so that the metal dry particle lines form a clear outline on the ceramic tile blank, enhancing the three-dimensional sense and artistic sense of the pattern. The entire process flow is reasonably designed, and each step is closely connected, from applying the base glaze to firing treatment, and ceramic tiles with enamel color decorative effects can be efficiently produced, thereby improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0046] Figure 1 This is a sample picture of a ceramic tile with enamel decorative effect on the surface prepared in Example 1 of the present application;
[0047] Figure 2 This is a sample picture of a ceramic tile with enamel decorative effect on the surface prepared in Example 2 of the present application. DETAILED DESCRIPTION
[0048] As used herein:
[0049] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0050] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0051] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0052] In these examples, parts and percentages are by mass unless otherwise indicated.
[0053] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0054] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0055] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0056] The present application provides a method for preparing a ceramic tile having an enamel decorative effect on the surface, comprising:
[0057] Apply base glaze and print color patterns on the surface of the tile blank in sequence;
[0058] Positioning metal dry particles on the tile blank formed with a color pattern to obtain the outline of the image lines outlined by the metal dry particles;
[0059] Print glue patterns, apply glassy dry particles, and spray suspended glaze slurry on the surface of the tile blank with image line contours;
[0060] The ceramic tile blanks sprayed with the suspended glaze slurry are fired to obtain ceramic tiles with enamel color decorative effects on the surface.
[0061] In the present application, metal dry particles are positioned on the ceramic tile blank with a color pattern, so that the metal dry particle lines form a clear outline on the ceramic tile blank, enhancing the three-dimensional sense and artistic sense of the pattern. The entire process flow is reasonably designed, and each step is closely connected, from applying the base glaze to firing treatment, and ceramic tiles with enamel color decorative effects can be efficiently produced, thereby improving production efficiency.
[0062] In some embodiments, the metal dry particles are positioned by dispensing with a glue dispenser; the glue is squeezed out through the needle of the glue dispenser and then covers the metal dry particles to fix the dry particles. After the glue solidifies, the metal dry particles are firmly fixed on the surface of the tile, and then the metal dry particles floating on the surface of the embryo that are not firmly positioned are removed.
[0063] In some embodiments, the metal dry particles are positioned by applying an electrostatic field to the surface of the tile blank for electrostatic adsorption. The electrostatic field enables the metal dry particles to overcome their own gravity and other resistances and be adsorbed at specific positions on the surface of the tile to form a line outline, and the metal dry particles that are not firmly adsorbed can be removed.
[0064] The preparation method of the present application introduces a positioning method of dispensing positioning by a dispensing machine or electrostatic adsorption positioning. Compared with existing cloisonné enamel, cloisonné glue drip enamel and other processes, it can obtain enamel decoration effects with rich colors, exquisite patterns, strong three-dimensional sense and artistic sense, while making the production process more stable and controllable, reducing scrap rate, improving production efficiency and reducing production costs.
[0065] It should be noted that the image line contours outlined by a dispensing machine or electrostatic adsorption technology in this application are unable to be accurately positioned for the silver paste, silver wire, etc. in existing enamel decorations by the dispensing machine or electrostatic adsorption technology. Therefore, in some embodiments, the metal dry particles include one or more of aluminum powder, copper powder, and iron powder; granular materials such as aluminum powder, copper powder, and iron powder are more suitable for use in dispensing machines or electrostatic adsorption technology. At the same time, the color and texture of silver paste and silver wire are relatively single, and aluminum powder, copper powder, and iron powder are conducive to obtaining a variety of decorative effects.
[0066] In addition, different metal materials may have different physical and chemical properties, such as hardness, melting point, affinity with glue, etc. These properties will affect the bonding effect between dry particles and tile surface and glue. Specifically:
[0067] (1) Aluminum, copper, and iron all have a certain hardness and can form relatively clear and lasting line contours on the surface of tiles. Compared with some softer materials, they are less likely to deform or wear during subsequent processing and use, and can better maintain the three-dimensional and artistic sense of the pattern.
[0068] (2) Aluminum powder, copper powder, and iron powder all have unique colors and lusters, which can add different visual effects to the decorative effects of tile surfaces. Copper powder can bring a golden or bronze luster, aluminum powder may present a silver or metallic texture, and iron powder may have a black or gray tone. Mixing aluminum powder, copper powder, and iron powder can create a more diverse combination of colors and textures. By adjusting the ratio of different metal powders, different tones and luster effects can be obtained to meet more personalized decorative needs. These rich colors can be combined with other decorative elements to create rich and diverse decorative effects.
[0069] (3) Aluminum powder, copper powder, and iron powder have good compatibility with common glues such as epoxy resin AB glue. The metal surface can form chemical bonds or adsorption with glue molecules. These physical and chemical effects can enhance the bonding force between glue and metal, making the metal dry particles more stably fixed on the tile surface.
[0070] (4) Aluminum, copper and iron have relatively good chemical stability under normal environmental conditions. They will not easily undergo chemical reactions on the surface of tiles to cause discoloration, corrosion and other problems, which is conducive to ensuring the durability of the decorative effect.
[0071] In some embodiments, the particle size of the metal dry particles is 0.1-0.5 mm, for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm or any value between 0.1-0.5 mm. First, the appropriate particle size can ensure the uniform distribution of the dry particles on the surface of the tile. Too large a particle size may cause the dry particles to accumulate, affecting the fineness and firmness of the pattern; too small a particle size may make it difficult for the surface dry particles to be effectively fixed by glue, and they are easy to fall off, and at the same time may cause the outlined image line contour to have a weak three-dimensional sense, thereby affecting the decorative effect; secondly, the appropriate particle size is conducive to the relative stability of the thermal expansion coefficient, and the thermal expansion coefficients of the glaze and the dry particles can be better matched during the firing process, which is conducive to inhibiting cracking caused by temperature changes; finally, the tile has high hardness and wear resistance, which requires the glaze and the dry particles to adapt to its surface characteristics during the firing process to avoid glaze peeling or dry particles falling off.
[0072] In some embodiments, the positioning of the metal dry particles satisfies at least one of the following features AC:
[0073] A. The dispensing speed of the dispensing machine is 10-20 times / second, the dispensing pressure is 0.2-0.5 MPa, the needle diameter of the dispensing machine is 0.2-0.5 mm, and the distance between the needle of the dispensing machine and the surface of the tile blank is maintained at 2-5 mm;
[0074] The dispensing speed of the dispensing machine is 10-20 times / second, for example, it can be 10 times / second, 12 times / second, 15 times / second, 18 times / second, 20 times / second or any value between 10-20 times / second. The appropriate dispensing speed is conducive to the glue being evenly applied on the surface of the brick and fully contacting with the metal dry particles. If the dispensing speed is too fast, it may cause uneven glue application and affect the fixing effect of the dry particles; if the dispensing speed is too slow, it will reduce production efficiency.
[0075] The dispensing pressure is 0.2-0.5 MPa, for example, it can be 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or any value between 0.2-0.5 MPa. Appropriate dispensing pressure can make the glue squeezed out and filled between the metal dry particles and the tile surface better, and enhance the bonding force between the metal dry particles and the tile surface. Too much pressure may cause the glue to overflow, affecting the beauty of the pattern and the positioning accuracy of the dry particles; too little pressure may not make the glue fully filled, resulting in the dry particles not being firmly fixed.
[0076] The needle diameter of the glue dispenser is selected according to the particle size and line profile requirements of the metal dry particles, preferably 0.2-0.5 mm. The appropriate needle diameter can ensure that the glue can be accurately applied around the metal dry particles and fully contact the dry particles and the tile surface. A needle diameter that is too large may cause glue waste and inaccurate positioning; a needle diameter that is too small may cause the glue to flow out poorly, affecting the fixation of the dry particles.
[0077] When dispensing glue, keep the distance between the needle and the surface of the ceramic tile 2-5 mm. This distance ensures that the glue can be evenly applied to the surface of the tile, avoiding poor contact between the glue and the tile surface or glue splashing. If the distance is too large, the glue may not be accurately applied around the dry particles; if the distance is too small, the needle may collide with the tile surface, damaging the needle or the tile surface, and also affecting the glue application effect.
[0078] B. The glue used in the glue dispensing machine is selected from epoxy resin AB glue, preferably bisphenol A epoxy resin, and the preferred models are E-44 bisphenol A epoxy resin and E-51 bisphenol A epoxy resin.
[0079] Different glue types and models may have differences in bonding performance, curing speed, temperature resistance, etc., which may affect the firmness of the dry particles. The epoxy resin in this application has good bonding performance, chemical corrosion resistance and mechanical strength, and can provide a good fixing effect for metal dry particles.
[0080] C. The glue dispensing machine is a double-liquid glue dispensing machine, and the glue used by the double-liquid glue dispensing machine includes glue A and glue B, and the glue A and the glue B are mixed in a mass ratio of 1:1 to 2:1.
[0081] The right mixing ratio can ensure the curing effect and bonding performance of the glue. If the mixing ratio is inappropriate, it may cause incomplete curing of the glue or decrease in bonding performance, thus affecting the firmness of the dry particle bonding.
[0082] D. The voltage of the electrostatic field is 10-30 kilovolts, the action time of the electrostatic field is 5-10 seconds, and the distance between the electrode applying the electrostatic field and the surface of the tile blank is 5-10 centimeters.
[0083] The voltage of the electrostatic field is 10-30 kilovolts. The higher the voltage, the stronger the electrostatic adsorption force, which will increase the bonding strength between the metal dry particles and the tile surface to a certain extent. However, too high a voltage may cause some adverse effects, such as partial discharge of the metal dry particles during the adsorption process, affecting the uniformity and stability of the adsorption, and may also have a certain impact on the electrical properties of the tile surface.
[0084] The action time of the electrostatic field is 5-10 seconds. Prolonging the action time appropriately can allow the metal dry particles to have more time to be adsorbed on the tile surface, thereby improving the bonding strength. However, after the adsorption process reaches saturation, further extending the action time will not further improve the bonding strength.
[0085] The distance between the electrode applying the electrostatic field and the surface of the tile blank is 5-10 cm. The appropriate distance can ensure that the electrostatic field produces a suitable electric field strength distribution on the surface of the tile, which is conducive to the uniform adsorption of the metal dry particles. If the distance is too close, the electric field strength may be uneven, affecting the uniformity and bonding strength of the adsorption; if the distance is too far, the electric field strength is weakened, which will reduce the adsorption force and bonding strength.
[0086] It should be noted that physical properties of tiles, such as surface roughness, may also affect electrostatic adsorption. A rougher surface may cause the metal dry particles to be less firmly adsorbed. Therefore, before applying electrostatic adsorption technology, the tile surface can be polished as needed.
[0087] In some embodiments, the viscosity of the glue used to print the glue pattern is 500-1000 centipoise;
[0088] And / or, the printing speed of the printed glue pattern is 10-20 m / min, and the amount of glue used is 10-20 g / m2;
[0089] And / or, the glue used for printing the glue pattern is acrylate glue; preferably, the acrylate glue is one or both of epoxy-modified acrylate glue and polyurethane-modified acrylate glue.
[0090] In some embodiments, the step of donating vitreous dry particles satisfies at least one of the following conditions:
[0091] a. The glassy dry particles are barium-containing glassy dry particles; the addition of barium can improve the glossiness and refractive index of the dry particles, and improve their bonding performance with the surface of the tile. This is because the barium ions can react chemically with the components on the surface of the tile during the firing process to form chemical bonds such as Ba-O, thereby enhancing the bonding strength.
[0092] b. The glassy dry particles are barium-containing glassy dry particles, and the barium-containing glassy dry particles include, by mass percentage: SiO2 55%-65%, BaO 15%-20%, Al2O3 10%-15% and Na2O 5%-10%;
[0093] Among them, SiO2 is one of the main components of glassy dry particles, providing the basic glassy structure for the dry particles; BaO provides barium element, which can improve gloss, refractive index and binding performance; Al2O3 helps to improve the hardness and chemical stability of the dry particles; Na2O can adjust the melting point and viscosity of glass, thereby affecting the processing and use performance of the dry particles.
[0094] c. More than 80 wt% of the glassy dry particles have a particle size between 0.1 and 0.5 mm; a suitable particle size distribution can ensure uniform distribution of the dry particles on the surface of the tile, avoiding accumulation or vacancies of the glassy dry particles.
[0095] d. The Mohs hardness of the glassy dry particles is between 5 and 7, which is beneficial to improving the wear resistance of enamel decoration.
[0096] e. The thermal expansion coefficient of the glassy dry particles is 50×10 -7 / ℃-80×10 -7 / ℃; similar to the thermal expansion coefficient of ceramic tiles, which helps to reduce the separation or cracking of dry particles from the ceramic tile surface due to temperature changes during firing and use.
[0097] f. The application speed of the glassy dry particles is 5-10 g / s; in some embodiments, the dry particles can be applied using a dry particle spreader.
[0098] The dispensing accuracy of the glassy dry particles is ±0.1 mm.
[0099] h. After applying the vitreous dry particles, a suction device is used to suck away the unbound vitreous dry particles; the suction force of the suction device is 10-20 Newtons, the diameter of the suction nozzle is 10-30 mm, and the action time is 5-10 seconds.
[0100] In some embodiments, the thickness of the base glaze is 0.1-0.3 mm; a suitable base glaze thickness can provide a good foundation for subsequent decorative layers. If the base glaze is too thick, it may cause defects such as bubbles during the firing process; if the base glaze is too thin, it cannot play a sufficient reinforcing and decorative foundation role.
[0101] In some embodiments, the viscosity of the base glaze tested with a No. 4 cup is 30-50 seconds and the specific gravity is 1.5-1.8 g / cm3. Appropriate viscosity can make the glaze evenly distributed on the surface of the tile to avoid sagging or uneven thickness. If the viscosity is too high, the glaze is difficult to spread evenly, which may cause excessive local thickness and affect the firing and decorative effects; if the viscosity is too low, the glaze may not be able to form a coating of sufficient thickness on the surface of the tile, affecting the decorative effect and protective effect. At the same time, the specific gravity of the base glaze will also affect the viscosity of the base glaze and the uniformity of the glaze, and a reasonable selection is required.
[0102] As the base layer, the uniformity and thickness of the base glaze will affect the bonding strength with the subsequent decorative layers (such as color pattern layer, dry particle layer, etc.). Base glaze with appropriate viscosity can better combine with the subsequent decorative layers and enhance the stability of the overall decorative effect.
[0103] The uniformity of the base glaze will also affect the final decorative effects of the ceramic tile, such as glossiness and color saturation. Base glaze with appropriate viscosity can provide a better foundation for subsequent decoration and make the decorative effect more outstanding.
[0104] It should be noted that in this application, the specific method of testing the viscosity of the glaze with a No. 4 cup is: at room temperature (about 25°C), pour the glaze into a No. 4 cup, let the glaze flow out naturally, and record the time from the beginning of flow to the end of flow. This time is the viscosity value of the glaze (in seconds).
[0105] In some embodiments, the color pattern is printed by a digital inkjet printer, the resolution of the digital inkjet printer is 300-600 dpi, and the viscosity of the ink is 10-20 centipoise. A clear and precise pattern is obtained. A higher resolution combined with a suitable adhesive ink can make the printed color pattern present a more delicate color transition and a clearer line contour on the ceramic tile blank, thereby better providing a background and foundation for subsequent decoration.
[0106] The purpose of printing color patterns is to provide a background and foundation for subsequent decoration, and the ink color can be selected according to the needs of the color pattern.
[0107] In some embodiments, the mass concentration of the suspending agent in the suspended glaze slurry is 40-60%;
[0108] And / or, the spraying pressure is 0.3-0.5 MPa;
[0109] And / or, the thickness of the suspended glaze slurry is 0.2-0.4 mm.
[0110] The suspended glaze slurry includes a suspending agent and a transparent glaze (conventional raw materials of Foshan Oushennuo Ceramics Co., Ltd.). The suspending agent makes it difficult for water to penetrate into the interior of the tile blank and can wrap the dry particles on the surface of the tile blank; the transparent glaze and the dry particles cooperate with each other to present a preset texture and decorative effect after firing.
[0111] Ways to enhance the effect: By controlling the concentration, pressure and thickness of the sprayed suspended glaze slurry, the surface texture and decorative effect of the ceramic tile can be enhanced. Specifically, the glaze slurry is evenly distributed on the surface of the ceramic tile to form a good glaze layer. Such a glaze layer can improve the surface flatness and brightness of the ceramic tile, and interact with the applied dry particles to further enrich and enhance the decorative effect of the ceramic tile. Specifically:
[0112] (1) Improve surface smoothness. When the suspended glaze slurry is sprayed on the surface of ceramic tiles, its uniform distribution can fill the tiny pores and unevenness on the surface of the tiles, forming a relatively flat covering layer on the surface of the tiles, thereby improving the surface smoothness of the ceramic tiles.
[0113] (2) Improve brightness. The components in the suspended glaze slurry will form a smooth surface structure after firing. On the one hand, the characteristics of the glaze slurry itself enable it to reflect more light and increase the glossiness of the ceramic tile surface; on the other hand, the appropriate spraying parameters ensure the uniformity and density of the glaze layer, reduce the scattering and absorption of light on the surface, and further improve the brightness.
[0114] (3) Interaction with dry particles enhances the decorative effect, including the improvement of color richness, three-dimensional effect and durability of decorative effect.
[0115] Color richness: The applied dry particles have different colors and luster (barium-containing glassy dry particles can enhance the luster, and there are also colored glassy dry particles or glassy dry particles with metallic luster to choose from). The suspended glaze slurry covers the dry particles, which not only protects the dry particles, but also makes the color of the dry particles more vivid and richer through the refraction and reflection of light, thus enhancing the color layering of the ceramic tile.
[0116] Enhanced three-dimensional effect: The dry particles form certain protrusions or textures on the surface of the ceramic tile, and the suspended glaze slurry fills between and around the dry particles, forming a three-dimensional decorative effect together with the dry particles. The presence of the glaze slurry makes the transition between the dry particles and the surface of the brick more natural, and also highlights the three-dimensional effect of the dry particles, making the decorative effect of the ceramic tile more vivid and realistic.
[0117] Durability of decorative effect: The suspended glaze slurry can protect the dry particles from erosion by the external environment, such as moisture, dust, etc. At the same time, its good combination with the dry particles can also prevent the dry particles from falling off, thus ensuring the durability of the decorative effect of the ceramic tile.
[0118] In some embodiments, the firing temperature is 1100-1300°C, and the firing time is 30-60 minutes. The firing temperature can be 1100°C, 1150°C, 1200°C, 1250°C, 1300°C or any value between 1100-1300°C, and the firing time can be 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, 60 minutes or any value between 30-60 minutes. Appropriate firing temperature and time can fully sinter the glaze and dry particles and firmly bond them to the tile matrix. If the temperature is too high or the time is too long, it may cause problems such as tile deformation and glaze cracking; if the temperature is too low or the time is too short, the glaze and dry particles may not be fully sintered, affecting the decorative effect and bonding strength.
[0119] (1) Changes in physical structure:
[0120] During the high-temperature firing process, the rising temperature will gradually discharge the water in the brick, which helps to improve the density and strength of the brick; at the same time, the temperature will cause the minerals in the brick to crystallize and reorganize, making the structure of the ceramic brick denser, thereby improving its hardness and wear resistance, making it more suitable for use as a building decoration material. For the dry particles applied on the surface of the brick, high-temperature firing will make them better integrated with the surface of the brick and the glaze layer, and the crystal structure inside may be more stable, forming a stronger bond with the brick and the glaze layer.
[0121] (2) Chemical changes: The chemical components in ceramic tiles will react at high temperatures.
[0122] The flux component in the ceramic tile blank may reduce the firing temperature and promote the melting and fusion of other components. Certain components in the glaze, such as barium, may react chemically with the surface of the dry particles to enhance the bonding between the dry particles and the glaze layer. During the firing process, some metal oxide components will undergo redox reactions at high temperatures, changing colors, thereby enriching the color expression of ceramic tiles.
[0123] The preparation method of the ceramic tile with enamel color decoration effect on the surface provided by the present application includes applying base glaze, printing color patterns, positioning metal dry particles, printing glue, applying glass dry particles, spraying suspended glaze slurry, and firing. Through the steps of positioning metal dry particles and applying glass dry particles, the ceramic tile presents a three-dimensional and artistic enamel color decoration effect with rich colors and exquisite patterns, which can meet the needs of consumers for high-end decorative materials. The production process of the preparation method of the present application is more stable and controllable, reducing the scrap rate, improving production efficiency, and reducing production costs; the entire process flow is reasonably designed, and the steps are closely connected. From applying base glaze to firing treatment, ceramic tiles with enamel color decoration effect can be efficiently produced, which improves production efficiency.
[0124] The preparation method of the present application can achieve a good match between materials, and ensure a firm bond between the enamel decorative layer and the tile substrate by optimizing the formula of glaze and dry particles and adjusting process parameters; reduce dependence on complex handicrafts, reduce production costs, and simplify the process flow by introducing advanced technologies such as digital inkjet printing and electrostatic adsorption; ensure that the decorative effect remains stable during long-term use by selecting materials with strong weather resistance and good adhesion, and optimize the firing process, thereby improving the stability and durability of the decorative effect; the preparation method of the present application is suitable for enamel decoration on the surface of ceramic tiles, meeting the market demand for diversified and high-quality ceramic tile decorations.
[0125] The present application also provides a ceramic tile with an enamel decorative effect on the surface, which is prepared by the above-mentioned method for preparing a ceramic tile with an enamel decorative effect on the surface.
[0126] The ceramic tile with enamel decorative effect on the surface of the present application can have a variety of choices. Different metal dry particles (such as aluminum powder, copper powder, iron powder, etc.) can be selected for positioning, and different types of glassy dry particles (barium-containing glassy dry particles, colored glassy dry particles, glassy dry particles with metallic luster, etc.) can be applied, providing designers and consumers with a wealth of decorative options to meet the decoration needs of different styles; it also has good bonding performance: epoxy resin glue is used to position the metal dry particles, and acrylic glue provides an adhesion basis for applying the dry particles, ensuring the firm adhesion of the dry particles on the surface of the ceramic tile blank and improving the durability of the product; high chemical corrosion resistance and mechanical strength: the epoxy resin glue and glassy dry particles in the present application have good chemical corrosion resistance and mechanical strength, so that the ceramic tile can maintain a good appearance and performance in various environments and is not easily damaged; good thermal stability: the carefully selected glassy dry particles have a suitable thermal expansion coefficient, and can stably adhere to the surface of the ceramic tile blank during the firing process, and are not prone to cracking, falling off, etc. due to temperature changes.
[0127] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0128] Example 1
[0129] Embodiment 1 provides a method for preparing a ceramic tile having an enamel decorative effect on the surface, comprising the following steps:
[0130] S1 Base glaze: Use the glaze pouring equipment to evenly pour the base glaze on the surface of the tile blank with a flat surface and no obvious defects. The thickness of the base glaze is controlled at 0.2 mm. The viscosity of the glaze is adjusted to 40 seconds (coating No. 4 cup), and the specific gravity is 1.6 g / cm3.
[0131] S2 Printing color pattern: Place the tile blank on the workbench of the digital inkjet printer, select the appropriate ink color according to the design requirements, set the printer resolution to 450dpi, and the ink viscosity to 15 centipoise.
[0132] S3 metal dry particle positioning (double liquid dispensing machine):
[0133] Prepare metal dry particles by mixing aluminum powder, copper powder and iron powder in a mass ratio of 1:1:1, and control the particle size to 0.3 mm.
[0134] Bisphenol A epoxy resins E-44 and E-51 were selected as glue A and glue B respectively, and were mixed in a mass ratio of glue A to glue B of 1.5:1.
[0135] Load the mixed glue into the glue dispensing machine, set the dispensing speed to 15 times / second, the dispensing pressure to 0.35 MPa, the needle diameter to 0.35 mm, adjust the distance between the needle and the tile blank surface to 3.5 mm, and use the glue dispensing machine to position the metal dry particles on the tile blank to complete the image line outline.
[0136] S4 prints glue pattern: Use glue printing equipment to print glue pattern on the surface of tile blank, select epoxy modified acrylate glue, control the glue viscosity to 750 centipoise, and print at a speed of 15 m / min.
[0137] S5 dry granules:
[0138] Barium-containing glassy dry particles were prepared, the chemical composition of which was SiO2: 60%, BaO: 18%, Al2O3: 12%, and Na2O: 10%.
[0139] Control the particle size distribution of dry particles to ensure that 85% of the dry particles are between 0.1-0.5 mm, Mohs hardness is 6, and the thermal expansion coefficient is 65×10 -7 / ℃.
[0140] Use a dispensing device to position and dispense dry particles at the location where the glue pattern is printed. The dispensing speed is 7.5 g / s and the dispensing accuracy is ±0.1 mm.
[0141] S6 sucks away unbonded dry particles: Use the suction device, set the suction force to 15 Newtons, the nozzle diameter to 20 mm, and the suction time to 8 seconds to suck away unbonded dry particles to ensure that the dry particles on the surface of the tile blank are evenly distributed and neat.
[0142] S7 Spraying suspended glaze slurry: Use suspended glaze slurry spraying equipment to spray suspended glaze slurry on the surface of the tile blank, control the concentration of the suspended glaze slurry to 50%, the spraying pressure to 0.4 MPa, and the spraying thickness to 0.3 mm.
[0143] S8 Firing treatment: Place the tile blank into the firing equipment for high temperature firing. The firing temperature is set to 1200°C and the firing time is 45 minutes. Figure 1 Ceramic tile samples with enamel decorative effect on the surface.
[0144] The ceramic tile prepared in Example 1 has the following advantages:
[0145] Rich and exquisite colors: The color pattern is printed by a digital inkjet printer with a resolution of 450dpi and an ink viscosity of 15 centipoise, which can present delicate color transitions and clear line contours, providing a beautiful background for subsequent decoration. Combined with the line contours outlined by the positioning of metal dry particles and the application of barium-containing glassy dry particles, the surface of the tile forms a rich sense of layering and three-dimensionality, with rich and varied colors and exquisite patterns. Figure 1 It can be seen that the decorative patterns on the surface of the tiles have a strong sense of art, and the combination of different colors and materials creates a unique visual effect.
[0146] Strong three-dimensional effect: The line contours formed by the positioning of metal dry particles and the applied glass dry particles form protrusions or textures on the surface of the tile, forming a certain height difference with the surface of the tile, producing a shadow effect under light, which enhances the three-dimensional effect.
[0147] Strong and durable: Through optimized process and material selection, as well as appropriate firing process, the dry particles are firmly attached to the surface of the tile blank, so that the tile has high chemical corrosion resistance and mechanical strength, can maintain good appearance and performance in long-term use, and is not easily damaged.
[0148] Example 2
[0149] Embodiment 2 provides a method for preparing a ceramic tile having an enamel decorative effect on the surface, comprising the following steps:
[0150] S1: Base glaze: same as in Example 1.
[0151] S2 Printing color pattern: Same as Example 1.
[0152] S3 metal dry particle positioning (electrostatic adsorption technology):
[0153] Prepare metal dry particles, the same as in Example 1.
[0154] An electrode is arranged near the surface of the tile blank, and a distance of 8 cm is maintained between the electrode and the surface of the tile blank.
[0155] A 20 kV electrostatic field is applied for 8 seconds, causing the metal dry particles to be adsorbed at specific locations, completing the outline of the image lines.
[0156] S4 printing glue pattern: same as in Example 1.
[0157] S5: administering dry particles: same as in Example 1.
[0158] S6 sucks away the unbound dry particles: same as in Example 1.
[0159] S7 spraying suspended glaze slurry: same as in Example 1.
[0160] S8 sintering treatment: same as in Example 1, Figure 2 A sample of ceramic tile with enamel decorative effect on the surface shown.
[0161] Example 3
[0162] This embodiment provides a method for preparing a ceramic tile having an enamel decorative effect on the surface, comprising the following steps:
[0163] S1 Base glaze: Use the glaze pouring equipment to evenly pour the base glaze on the surface of the tile blank with a flat surface and no obvious defects. The thickness of the base glaze is controlled at 0.15 mm. The viscosity of the glaze is adjusted to 35 seconds (coating No. 4 cup), and the specific gravity is 1.55 g / cm3.
[0164] S2 Printing color pattern: Place the tile blank on the workbench of the digital inkjet printer, select the appropriate ink color according to the design requirements, set the printer resolution to 500dpi, and the ink viscosity to 12 centipoise.
[0165] S3 Metal Dry Particle Positioning (Dispensing Machine)
[0166] Prepare metal dry particles, which are made by mixing aluminum powder and copper powder in a mass ratio of 2:1, and the particle size is controlled at 0.2 mm.
[0167] Use bisphenol A epoxy resin E-44 as glue, load the glue into the glue dispensing machine, set the dispensing speed to 12 times / second, the dispensing pressure to 0.3 MPa, the needle diameter to 0.3 mm, adjust the distance between the needle and the tile blank surface to 3 mm, and use the glue dispensing machine to position the metal dry particles on the tile blank to complete the image line contour.
[0168] S4 prints glue pattern: Use glue printing equipment to print glue pattern on the surface of tile blank, select polyurethane modified acrylate glue, control the glue viscosity to 600 centipoise, and print at a speed of 12 m / min.
[0169] S5 dry granules
[0170] Barium-containing glassy dry particles were prepared, and the chemical composition (mass percentage) thereof was: SiO2: 62%, BaO: 16%, Al2O3: 13%, Na2O: 9%.
[0171] The particle size distribution of the dry particles is controlled to ensure that 82% of the dry particles have a particle size between 0.1 and 0.5 mm, a Mohs hardness of 5.5, and a thermal expansion coefficient of 70×10-7 / °C.
[0172] Use a dispensing device to position and dispense dry particles at the location where the glue pattern is printed. The dispensing speed is 6 g / s and the dispensing accuracy is ±0.1 mm.
[0173] S6 sucks away unbonded dry particles: Use the suction device, set the suction force to 12 Newtons, the nozzle diameter to 15 mm, and the suction time to 6 seconds to suck away unbonded dry particles to ensure that the dry particles on the surface of the tile blank are evenly distributed and neat.
[0174] S7 Spraying suspended glaze slurry: Use suspended glaze slurry spraying equipment to spray suspended glaze slurry on the surface of the tile blank, control the concentration of the suspended glaze slurry to 45%, the spraying pressure to 0.35 MPa, and the spraying thickness to 0.25 mm.
[0175] S8 Firing treatment: Place the ceramic tile blank into a firing device for high-temperature firing. The firing temperature is set to 1150°C and the firing time is 40 minutes to obtain a ceramic tile sample with an enamel decorative effect on the surface.
[0176] Comparative Example 1 (Irrational selection of metal dry particles)
[0177] This comparative example provides a method for preparing a ceramic tile with an enamel decorative effect on the surface. The main difference from Example 1 is that the metal dry particles are different. The metal dry particles are pure silver powder, and the particle size is also controlled at 0.3 mm.
[0178] Comparative Example 2 (Dispensing machine parameters are unreasonable)
[0179] This comparative example provides a method for preparing a ceramic tile with an enamel decorative effect on the surface, which is different from Example 1 mainly in the parameter setting of the glue dispenser. In Comparative Example 2, the glue dispensing speed is 5 times / second, the glue dispensing pressure is 0.1 MPa, the needle diameter is 0.2 mm, and the distance between the needle and the surface of the ceramic tile is 1 mm.
[0180] Comparative Example 3 (Unreasonable Firing Temperature)
[0181] This comparative example provides a method for preparing a ceramic tile with an enamel decorative effect on the surface, which is different from Example 1 mainly in the firing temperature. In Comparative Example 3, the firing temperature is set to 900° C. and the firing time is 45 minutes.
[0182] The performance of the ceramic tiles with enamel decorative effect on the surface prepared in the above embodiments and comparative examples was tested, and the specific testing method is as follows:
[0183] Peel test: The force required is measured by gradually peeling off the interface between the enamel layer and the tile substrate. Standard: ASTM D903-2017 "Standard Test Method for Peel or Stripping Strength of Adhesive Bonds".
[0184] Bending test: Testing the bonding strength by applying bending stress. Standard: GB / T 4100-2015 "Ceramic Tiles" Appendix C "Ceramic Tiles Bending Strength Test Method".
[0185] Thermal shock resistance test: Heat and cool the ceramic tile between 145℃±5℃ and 15℃±5℃, repeat the heating and cooling process 10 times, and check the damage of the sample. Standard: GB / T 3810.9-2016 "Test methods for ceramic tiles Part 9: Determination of thermal shock resistance".
[0186] Accelerated aging test: simulates the effects of environmental factors that ceramic tiles may encounter during long-term use on their performance. Standard: GB / T 1865-2009 "Artificial weathering and artificial radiation exposure of paints and varnishes (filtered xenon arc radiation)"
[0187] Adhesion of decorative layer (cross-cut test method): Evaluate the adhesion between the enamel decorative layer and the tile substrate. Standard: GB / T 9286-1998 "Cross-cut test for paint and varnish films".
[0188] The test results are shown in Table 1.
[0189] Table 1
[0190]
[0191]
[0192] Examples 1-3
[0193] The metal dry particles are reasonably selected: a mixture of aluminum powder, copper powder and iron powder is used, which not only provides good gloss but also has excellent adhesion and durability.
[0194] Optimization of dispensing parameters: By adjusting the dispensing speed, pressure, needle diameter and the distance between the needle and the tile surface, uniform application of glue and firm adhesion of dry particles are ensured.
[0195] Appropriate firing temperature: The optimized firing temperature is used to fully sinter the glaze and dry particles, enhancing the bonding between them.
[0196] The test results are excellent: it performed well in the peeling test, bending test, thermal shock resistance test and decorative layer adhesion test, with each index being 2, indicating that the durability and stability of the decorative effect are very good.
[0197] Comparative Example 1: Unreasonable selection of metal dry particles
[0198] Although silver powder has a high glossiness, its adhesion and durability are poor, and it is easy to fall off during use, affecting the durability of the decorative effect. In contrast, the mixture of aluminum powder, copper powder and iron powder used in Example 1 has better adhesion and durability.
[0199] Comparative Example 2 (Dispensing machine parameters are unreasonable)
[0200] The dispensing speed was too slow, the pressure was too low, the needle diameter was too small, and the distance between the needle and the tile surface was too close, resulting in uneven glue application and weak fixation of the dry particles. In contrast, the optimized dispensing parameters in Example 1 ensured the firm attachment of the dry particles and the durability of the decorative effect.
[0201] Comparative Example 3 (Unreasonable Firing Temperature)
[0202] The firing temperature is too low, resulting in the glaze and dry particles not being fully sintered, the bonding force is weak, and they are easy to fall off during use. In contrast, the optimized firing temperature in Example 1 ensures that the glaze and dry particles are fully sintered and firmly bonded, improving the durability and stability of the decorative effect.
[0203] Through the analysis of comparative examples 1, 2, and 3, combined with the results of examples 1, 2, and 3, the selection of metal dry particles, the parameter settings of the dispensing machine and electrostatic adsorption, and the firing temperature have a significant impact on the decorative effect and durability of the tile. The optimized materials and process parameters in Example 1 ensure the high quality and durability of the enamel decorative effect on the surface of the tile, showing the advantages of the technical solution of the present application.
[0204] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0205] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a ceramic tile having an enamel decorative effect on the surface, characterized in that: include: Apply base glaze and print color patterns on the surface of the tile blank in sequence; Positioning metal dry particles on the tile blank formed with a color pattern to obtain the outline of the image lines outlined by the metal dry particles; Print glue patterns, apply glassy dry particles, and spray suspended glaze slurry on the surface of the tile blank with image line contours; The ceramic tile blanks sprayed with the suspended glaze slurry are fired to obtain ceramic tiles with enamel color decorative effects on the surface.
2. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 1, characterized in that: The metal dry particles are positioned by dispensing with a dispensing machine; Alternatively, the metal dry particles are positioned by electrostatic adsorption by applying an electrostatic field on the surface of the tile blank.
3. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 1, characterized in that: The metal dry particles include one or more of aluminum powder, copper powder, and iron powder; And / or, the particle size of the metal dry particles is 0.1-0.5 mm.
4. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 2, characterized in that: The positioning of the metal dry particles meets at least one of the following features AD: A. The dispensing speed of the dispensing machine is 10-20 times / second, the dispensing pressure is 0.2-0.5 MPa, the needle diameter of the dispensing machine is 0.2-0.5 mm, and the distance between the needle of the dispensing machine and the surface of the tile blank is maintained at 2-5 mm; B. The glue used in the glue dispensing machine is selected from bisphenol A type epoxy resin; C. The dispensing machine is a double-liquid dispensing machine, and the glue used by the double-liquid dispensing machine includes glue A and glue B, and the glue A and the glue B are mixed in a mass ratio of 1:1 to 2:1; D. The voltage of the electrostatic field is 10-30 kilovolts, the action time of the electrostatic field is 5-10 seconds, and the distance between the electrode applying the electrostatic field and the surface of the tile blank is 5-10 centimeters.
5. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 1, characterized in that: The viscosity of the glue used for printing the glue pattern is 500-1000 centipoise; And / or, the printing speed of the printed glue pattern is 10-20 m / min; And / or, the glue used for printing the glue pattern is acrylate glue; preferably, the acrylate glue is one or both of epoxy-modified acrylate glue and polyurethane-modified acrylate glue.
6. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 1, characterized in that: The step of donating glassy dry particles satisfies at least one of the following conditions: a. The vitreous dry particles are barium-containing vitreous dry particles; b. The glassy dry particles are barium-containing glassy dry particles, and the barium-containing glassy dry particles include, by mass percentage: SiO255%-65%, BaO 15%-20%, Al2O3 10%-15% and Na2O 5%-10%; c. more than 80 wt% of the glassy dry particles have a particle size between 0.1 and 0.5 mm; d. The Mohs hardness of the glassy dry particles is between 5 and 7; e. The thermal expansion coefficient of the glassy dry particles is 50×10 -7 / ℃-80×10 -7 / ℃; f. The application rate of the glassy dry particles is 5-10 g / sec; The dispensing accuracy of the glassy dry particles is ±0.1 mm; h. After applying the vitreous dry particles, a suction device is used to suck away the unbound vitreous dry particles; the suction force of the suction device is 10-20 Newtons, the diameter of the suction nozzle is 10-30 mm, and the action time is 5-10 seconds.
7. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 1, characterized in that: The thickness of the base glaze is 0.1-0.3 mm; And / or, the viscosity of the base glaze tested by applying a No. 4 cup is 30-50 seconds and the specific gravity is 1.5-1.8 g / cm3; And / or, the color pattern is printed by a digital inkjet printer, the resolution of the digital inkjet printer is 300-600 dpi, and the viscosity of the ink is 10-20 centipoise.
8. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 1, characterized in that: The mass concentration of the suspending agent in the suspended glaze slurry is 40-60%; And / or, the spraying pressure is 0.3-0.5 MPa; And / or, the thickness of the suspended glaze slurry is 0.2-0.4 mm.
9. The method for preparing a ceramic tile having an enamel decorative effect on the surface according to claim 1, characterized in that: The firing temperature is 1100-1300° C., and the firing time is 30-60 minutes.
10. A ceramic tile with enamel decorative effect on the surface, characterized in that: The ceramic tile having enamel decorative effect on the surface is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Stereo-positioning effect dry granule complete-polished ceramic brick and preparation method thereof
CN110396005A
Enamel color material, preparation method thereof, and application in porcelain body painting enamel cultural relic repair
CN110713345A
Production process of ceramic tile with stereotactic dry particles, and product thereof
CN112010676A
Cloisonne colored porcelain and preparation process thereof
CN112759261A
Dry -particle decorative ceramic tile and preparation method thereof
CN113248285A
Cited By
Charge positioning platinum / gold dry particle, ceramic tile and preparation method of charge positioning platinum / gold dry particle
CN120736798A
Charge localization platinum / gold dry pellets, tiles, and methods of making the same
CN120736798B
Environment-friendly concave-convex embossment colored ceramic tile and preparation method thereof
CN120829319A